Contribution to methods and techniques of scientific research: Process of publishing a scientific manuscript - Ranković Nenad (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu)
In order for authors, especially younger ones, to know what they have to count on in the process of publishing their manuscripts, they need to know that process and adequately prepare for everything that awaits them. In this explanation, the focus is on the process of publishing a manuscript in a scientific journal, in the classic way (printing on paper). However, the process is very little different for other types of documents or for electronic publications. The main characteristic of the manuscript publishing process is the relative complexity and multiple sending and returning of the manuscript (from the author to the editorial office and back). This requires that the authors and editors of the magazine have a lot of patience and show promptness and cooperation in mutual communication.